Improving Counting Skills Adding Natural Numbers 1 – 100 For Students with Autism Through Smart Board - Yunisa, Fitriza; Damri, Damri; Sopandi, Asep Ahmad; Efrina, Elsa (Edumaspul: Jurnal Pendidikan, 2024)
This research focuses on improving the ability to calculate adding natural numbers 1 - 100 for students with autism at SLB Insan Mulia Payakumbuh using smart board media. Smart board media is a two-dimensional media in the form of a board that gives messages to the target and makes it easier for students to operate and understand additions properly and correctly. This research uses a quantitative approach with experimental methods, namely Single Subject Research (SSR) and A1-B-A2 Design, and data is analyzed using visual graphs by entering data in graphs which are then analyzed based on conditions A1-B-A2. The results of research using smart board media can improve the ability to calculate adding natural numbers 1-100 for students with autism at SLB Insan Mulia Payakumbuh.